A simple and low-cost chip bonding solution for high pressure, high temperature and biological applications. Issue 4 (23rd January 2017) - Serra, M.; Pereiro, I.; Yamada, A.; Viovy, J.-L.; Descroix, S.; Ferraro, D.
Abstract : An adhesive-based strategy for the low-cost and reversible sealing of a wide range of materials used in microfluidics, requiring only the application of manually-achievable pressures. Abstract : The sealing of microfluidic devices remains a complex and time-consuming process requiring specific equipment and protocols: a universal method is thus highly desirable. We propose here the use of a commercially available sealing tape as a robust, versatile, reversible solution, compatible with cell and molecular biology protocols, and requiring only the application of manually achievable pressures. The performance of the seal was tested with regards to the most commonly used chip materials. For most materials, the bonding resisted 5 bars at room temperature and 1 bar at 95 °C. This method should find numerous uses, ranging from fast prototyping in the laboratory to implementation in low technology environments or industrial production.